2018
DOI: 10.2118/181408-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Step Change for Single-Well Chemical-Tracer Tests: Field Pilot Testing of New Sets of Novel Tracers

Abstract: Summary The single-well chemical-tracer test (SWCTT) is an in-situ test to measure oil saturation, and has been used extensively to assess the potential for enhanced oil recovery (EOR) or to qualify particular EOR chemicals and methods. An SWCTT requires that a primary tracer be injected and that a secondary tracer be generated from the primary tracer in situ. Typically, a few hundred liters of ester is injected as primary tracer, and the secondary tracer is formed through hydrolysis in the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…It was necessary to identify and quantify these compounds in produced waters from oilfield in concentrations of low µg/L, or, ideally, even lower. The lowest possible LOQs are desirable to increase the accuracy of the recorded tracer production curves while simultaneously reducing the amount of chemicals used in the test (AlAbbad et al, 2018;. This is particularly an important factor in offshore operations due to HSE and logistic issues and large well distances.…”
Section: Development Of An Analytical Methods For Real Field Samplesmentioning
confidence: 99%
“…It was necessary to identify and quantify these compounds in produced waters from oilfield in concentrations of low µg/L, or, ideally, even lower. The lowest possible LOQs are desirable to increase the accuracy of the recorded tracer production curves while simultaneously reducing the amount of chemicals used in the test (AlAbbad et al, 2018;. This is particularly an important factor in offshore operations due to HSE and logistic issues and large well distances.…”
Section: Development Of An Analytical Methods For Real Field Samplesmentioning
confidence: 99%
“…The fluorescent polymer microspheres tracers prepared as 0.2 mg/L fracturing fluid suspension and heated at different temperatures (25,50,80,110, and 140 C) for 1 h, then the fluorescence emission spectra of the mixture were tested after it cooled down to room temperature. The pH of the aqueous solution was adjusted by sodium hydroxide and hydrochloric acid, and then a 0.2 mg/mL suspension of the fluorescent polymer microspheres was prepared to test the fluorescence emission spectra at different pH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The suspension of fluorescent polymer microspheres was also left under natural conditions for 30 days and their fluorescence emission spectra were S C H E M E 1 Synthesis route of fluorescent microspheres tested every 5 days.…”
Section: The Testing Of Performance About the Fluorescent Polymer Mic...mentioning
confidence: 99%
“…[7][8][9] The tracers can return the underground situation to the ground through signals, which can better assist in the field survey of oil reservoirs (including inter-well connections, inter-layer connections and heterogeneity). [10][11][12] Many tracers have been used in dynamic monitoring, evaluation of oilfield production, 13,14 improving recovery measures and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al reported that the combination of tracer data, completion data and also stimulation data in a machine-learning framework could show better dynamic behavior in a fracture network system 29 . Also a brief history of activities performed in the analysis of tracers is presented in Appendix C 11 , 12 , 16 , 18 , 24 , 30 57 .…”
Section: Introductionmentioning
confidence: 99%